PENGELOLAAN PENDIDIKAN AGAMA ISLAM PADA MASA PANDEMI COVID 19 DI SMA NEGERI 4 SIBOLGA - MS, Amiruddin; Siregar, Syahrul Mahyuddin; Zunidar, Zunidar (Prodi PGMI STIT Al-Ittihadiyah Labuhanbatu Utara, 2021)
The results of this study reveal three findings, namely: First, the learning management plan during the Covid 19 pandemic at SMA Negeri 4 Sibolga, it can be concluded: PAI learning management about learning models, sorting out the basic competencies that are taught, the time and the system used. Second, the management of Islamic Education learning during the Covid-19 pandemic at SMA Negeri 4 Sibolga was carried out by means of an online network for students who have devices, internet data packages or slumber, and offline learning for students who do not have devices, internet data packages or pulses. Online is done by utilizing the WhatsApp application, zoom, youtube, google classroom and learning web pages. While offline is carried out through the provision of books, modules, and worksheets which are picked up and delivered directly by students to school. There are also limited face-to-face meetings at mosques or locations deemed appropriate. Third, evaluation of implementation. Distance learning with online and offline models is considered less optimal in the delivery of material because educators cannot ensure the condition of students in following learning, and students' interest in learning is low and decreasing and learning outcomes are not objective.